The Impact of Social Media on Global Political Stability: A Quantitative Analysis of Democratic Governance and Political Communication - Arwarkh Fauzi Ramadhan (IHSA Institute, 2026)
The rapid expansion of social media has fundamentally transformed political communication, governance, and citizen engagement worldwide, making digital platforms essential channels for information dissemination, political participation, and public discourse. While social media enhances democratic participation by increasing political awareness, civic engagement, and government transparency, it also presents significant challenges through the spread of misinformation, disinformation, political polarization, and online extremism that may undermine political stability. This study aims to examine the influence of social media on global political stability by evaluating both its positive and negative political impacts. A quantitative research approach employing a cross-sectional survey design was adopted. Data were collected through structured questionnaires administered to 400 active social media users selected using stratified random sampling. The collected data were analyzed using descriptive statistics, reliability and validity testing, and Structural Equation Modeling (SEM) to examine the relationships between social media influence and political stability. The findings reveal that social media has a statistically significant and overall positive influence on global political stability by enhancing political awareness, citizen participation, government transparency, and democratic accountability. However, the results also indicate that fake news, coordinated disinformation, echo chambers, political polarization, election interference, and online harassment remain critical threats to democratic governance and institutional trust. These findings suggest that maximizing the democratic benefits of social media requires responsible platform governance, strengthened digital literacy, effective fact-checking mechanisms, transparent political communication, and evidence-based regulatory policies that protect freedom of expression while minimizing the adverse effects of online misinformation and political manipulation.